Maternal mortality in tertiary care hospital: a 2-year review - Patel, Juhi Ankit; Nakum, Kanaklata D.; Vithal, Aditi; Lunagariya, Mayank R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Epidemiological data pertaining to maternal mortality is valuable in each set up to design interventional programs to favourably reduce the ratio. This study was done to evaluate the maternal mortality rate in our hospital, to assess the epidemiological aspects and causes of maternal mortality, and to suggest recommendations for improvement. Methods: This was a 2-year retrospective study. Epidemiological data was collected from the Last 2 years of Facility Based Maternal Death Review Form. Maternal mortality ratio, epidemiological factors and causes affecting maternal mortality were assessed. Results: A total of 72 maternal deaths occurred. Most maternal deaths occurred in the age group of 20–24 years (40.27%), multiparous women (70.83%), women from rural areas (65.27%), illiterate women, unbooked patients (83.33%), and patients of low socioeconomic status. Direct causes accounted for 62.4% of maternal deaths where as 37.4% of maternal deaths were due to indirect causes. Conclusions: There is a wide scope for improvement as a large proportion of the observed deaths could be preventable.